Durability study of AAMs: Sulfate attack resistance. (30th December 2019) - Aliques-Granero, Josep; Tognonvi, Monique Tohoue; Tagnit-Hamou, Arezki
Graphical abstract: Highlights: High curing temperature of OPC mortar foster expansion due to sulfate attack. AAM systems better withstand sulfate attack than the ones of OPC. Curing temperature required before sulfate attack depends on the material source. Dimension and mass changes not suitable to assess degree of sulfate attack for AAM. Microstructural characterization used to identify attack product. Abstract: This paper is a part of works intended to determine more appropriate durability test methods for alkali activated materials (AAMs). Indeed, the current methods used to characterize durability of AAMs are those initially developed for ordinary Portland cement (OPC) and blended OPC. As the chemistry that governs both AAMs and OPC systems is completely different, using OPC durability methods for AAMs could induce inaccurate results. This work aims to study sulfate resistance of alkali activated slag (AAS), alkali activated fly ash (AAFA) and OPC (used as reference) to propose appropriate sulfate resistance test for AAMs by using ASTM C1012 as a basis. Both temperature of curing and sodium sulfate concentration were studied. Expansion of samples was evaluated over time. Results showed that all the OPC bars exceeded the limit compliance with less expansion for those precured at 35 °C. The expansion was attributed in all cases to gypsum and ettringite formation. AAS samples underwent expansion that remains below the limit compliance. At high curing temperature, an initial high expansion attributed to water absorption by the formed porosity was observed. For AAFA systems, no expansion was detected whatever the curing regime and the sulfate concentration, showing a great resistance of such systems to sodium sulfate attack.